2023
DOI: 10.1108/techs-07-2023-0025
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the adoption of cryptocurrency in Bangladesh: an investigation using the technology acceptance model (TAM)

Hasibul Islam,
Masud Rana,
Shimanto Saha
et al.

Abstract: PurposeUsing the technology acceptance model (TAM), this study investigates factors influencing the adoption of cryptocurrency in Bangladesh.Design/methodology/approachData were collected from 346 members of the general public through a structured web survey using snowball sampling. Structural equation modeling was used to analyze the data and assess the reliability and validity of the measurement model.FindingsThe results show that knowledge of cryptocurrency, benefits of use (perceived usefulness), attitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…To better understand the factors influencing users’ attitudes and behaviors toward MFS, it is essential to examine the underlying determinants and their relationships. Previous studies have identified a broad range of significant predictors, including perceived usefulness (PU), perceived ease of use (PEOU), subjective norms, perceived benefits (functional and emotional), consumer innovativeness, demographics, perceived risk and facilitating conditions (Islam et al ., 2023; Al-Saedi et al ., 2020; Chi, 2018; Davis et al ., 1989; Gupta and Manrai, 2018; Himel et al ., 2021; Işık et al ., 2024; Jung et al ., 2020; Manrai and Gupta, 2020; Yen and Wu, 2016; Rana et al ., 2023). These factors influence users’ attitudes and behavioral intentions through the lens of the technology acceptance model (TAM) and related behavioral theories.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the factors influencing users’ attitudes and behaviors toward MFS, it is essential to examine the underlying determinants and their relationships. Previous studies have identified a broad range of significant predictors, including perceived usefulness (PU), perceived ease of use (PEOU), subjective norms, perceived benefits (functional and emotional), consumer innovativeness, demographics, perceived risk and facilitating conditions (Islam et al ., 2023; Al-Saedi et al ., 2020; Chi, 2018; Davis et al ., 1989; Gupta and Manrai, 2018; Himel et al ., 2021; Işık et al ., 2024; Jung et al ., 2020; Manrai and Gupta, 2020; Yen and Wu, 2016; Rana et al ., 2023). These factors influence users’ attitudes and behavioral intentions through the lens of the technology acceptance model (TAM) and related behavioral theories.…”
Section: Introductionmentioning
confidence: 99%